1998
DOI: 10.1093/emboj/17.6.1728
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative interaction of Ets-1 with USF-1 required for HIV-1 enhancer activity in T cells

Abstract: The distal enhancer region of the human immunodeficiency virus 1 (HIV-1) long terminal repeat (LTR) is known to be essential for HIV replication and to contain immediately adjacent E-box and Ets binding sites. Based on a yeast one-hybrid screen we have identified the E-box binding protein USF-1 as a direct interaction partner of Ets-1 and found that the complex acts on this enhancer element. The binding surfaces of USF-1 and Ets-1 map to their DNA-binding domains and although these domains are highly conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
99
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 57 publications
4
99
0
Order By: Relevance
“…This is supported by the finding that phosphorylation of Sp1 and PU.1 are increased as myeloid cells differentiate (52,59). A second mechanism suggested by Sieweke et al (56) suggests that ets-1 and USF-1 interact to form a complex, resulting in exposure of the respective DNA-binding domains of each factor. According to both of these models a ternary complex would exist that should be detectable by EMSA.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is supported by the finding that phosphorylation of Sp1 and PU.1 are increased as myeloid cells differentiate (52,59). A second mechanism suggested by Sieweke et al (56) suggests that ets-1 and USF-1 interact to form a complex, resulting in exposure of the respective DNA-binding domains of each factor. According to both of these models a ternary complex would exist that should be detectable by EMSA.…”
Section: Discussionmentioning
confidence: 82%
“…Although these factors are ubiquitously expressed, an increasing number of studies have appeared in the past several years demonstrating a role for USF in the regulation of tissue-specific genes. USF binding has been shown to be required for human immunodeficiency virus type-1 enhancer activity in T cells (56) and for regulation of expression of the surfactant protein-A gene (57). Involvement of USF in myeloid cell differentiation was suggested by Kreider et al (58) and Suzow and Friedman (25) reported that deletion of the E box in the myeloperoxidase gene reduced promoter activity by 5-fold.…”
Section: Discussionmentioning
confidence: 95%
“…For example, interaction between Ets1 and USF-1 results in cooperative activation of the human immunodeficiency virus, type I, promoter. The consensus site for USF-1 and the transcriptional activation domain of Ets1 are both required for this effect, whereas a functional ETS-binding site is not (22). Thus ETS proteins can be recruited to promoters and contribute to transcriptional regulation without directly binding to DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these factors are induced by CD28 signaling, and can bind sites within the HIV-1 long terminal repeat (LTR) and activate HIV-1 transcription (29,(32)(33)(34). Furthermore, the viral transcriptional trans activator Tat is necessary for efficient transcription.…”
Section: P Roductive Infection Of Cd4mentioning
confidence: 99%